PENERAPANMMODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DISERTAI MEDIA POWERPOINT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DI SMA N 3 SRAGEN PADA MATA PELAJARAN EKONOMI TAHUN AJARAN 2017/2018 - -, Akmal Muzaki -; -, Soetarno Joyoatmojo -; -, Dewi Kusuma Wardani - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The purpose of this research was to improve student achievement through cooperative learning models with the type of Think Pair Share accompanied by Powerpoint media on Economics subjects metter of class X IPS 4 in Sragen 3 State Senior High School. This research is a Grade Action Research. The research was carried out in 2 cycles, each cycle consisting of planning, implementing, observing, and reflecting. The research subjects were students of class X IPS 4 in Sragen 3 State Senior High School, amounting to 36mstudents. Data collection techniques used are affectivepaspect observation, interviews, cognitive outcome tests, and documentation. Datapvalidity with data source triangulation techniques and method triangulation. Data analysis techniques with quantitative data analysis, qualitative and comparativepdescriptive.Based on the results of the analysis there was a significant increase in student achievement from pre-cycle to cycle I to cycle II. This can be seen in the results of the pre-cycle assessment with an average of 71 student learning achievements and a percentage of completeness of 58%. In cycle I when applied cooperative learning type Think Pair Share accompanied by Powerpoint media student achievement increased 75 and the percentage of completeness was 72%. Then in the second cycle there was an increase in the results of student learning achievement to 80 and the percentage of completeness 81%..The conclusion of this study is that through the cooperative learning model type Think Pair Share accompanied by Powerpoint media students are more daring to express opinions when discussing, fun and learning achievement has increased so that the application of cooperative learning model type Think Pair Share accompanied by Powerpoint media can improve the learning achievement of grade X students. IPS 4 in Sragen 3 State Senior High School in Economics subjects metter 2017/2018 academic year.